Altruistic Behavior in the Diversity of the Cigugur Community, Kuningan - Nadzirah, Salma; Yoselisa, Dani (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2025)
The main problem in this thesis is motivated by the phenomenon in Cigugur Village, Kuningan Regency, which is a miniature of Indonesia where there are various religions, ethnicities and cultures. The diversity of religions, ethnicities and cultures is not used as a reason for separation but as a force to strengthen unity and create harmony. This diversity is the background in observing how the attitude of helping and assisting in the midst of society, this attitude is called altruism. This study aims to describe altruistic behavior in the community living in diversity in Cigugur, Kuningan Regency. This study employed qualitative research with a field research approach and ethnographic methods. Data were collected through observation and semi-structured interviews with participants from various religious and cultural backgrounds living in Cigugur Village. The subjects of this study consisted of three religious leaders and four community members, using human instruments. The data sources used were primary and secondary sources. This study also employed data analysis techniques, namely data reduction, data presentation, and conclusions. The results of this study indicate that altruistic behavior in the Cigugur community, Kuningan, has become part of everyday life. Altruistic behavior is found in celebrations, funerals, religious holidays, and traditional activities, carried out regardless of background. Forms of altruism are reflected in empathy, belief in world justice, social responsibility, internal self-control, and low ego. Factors that encourage this behavior are religious teachings, cultural values that emphasize the importance of mutual cooperation, and belief in a harmonious social environment. Individual awareness and shared values are a strong foundation in creating tolerance and caring for others. The results also show no inhibiting factors in altruistic behavior in the diverse Cigugur community.